Pengaruh Kemampuan Berbahasa Indonesia Terhadap Efektivitas Komunikasi di Kantor - Nabila, Adinda Fakhira; Febrian, Aditia; Hasanah, Aghnia Qalbi; Azizan, Aidil Asfa; Natasha, Alexandra; Kodriyanti, Alya Sopwa; Rizkyanfi, Mochamad Whilky (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the extent to which proficiency in the Indonesian language affects communication effectiveness in the workplace. Through a literature study approach, this research gathers various theories and research findings from trustworthy academic sources. Research data is obtained through the collection of various written sources, including scientific journals, research reports, monographs, and official documents, both in print and digital forms. The data analysis process is conducted using content analysis techniques. The findings show that Indonesian language skills, both verbally and in writing, significantly contribute to improving the clarity and efficiency of communication in the office. In addition, language also plays an important role in building an inclusive and harmonious work atmosphere. The results of this study are expected to contribute to improving organizational communication practices and developing employee language skills.